Perception of private practitioners towards diagnosis and treatment of tuberculosis in Hubballi city, India - Patil, Sachin Kumar; Bathija, Geeta V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Private sector accounts more than third of all out- patient visit in India. For Revised Nation Tuberculosis Control Programme (RNTCP) to broaden its reach and have maximum impact, the involvement of private practitioners (PPs) in the programme plays a prime role. Objectives of the study were to assess the knowledge, attitude and practice of PPs about diagnosis and management of tuberculosis patient and their involvement RNTCP. Methods: A cross sectional study was conducted among 120 private medical practitioners of Hubballi Taluk, Dharwad district, Karnataka during June-July 2017. Using a pre-designed and semi-structured questionnaire data regarding their specialization, TB management practices, attitude towards DOTS (Directly Observed Treatment -short course), barriers in referring to RNTCP and notification from PPs at their clinic was collected. Results: Cough with sputum not relieved with antibiotics lead to suspicion of tuberculosis according to 80.8% of practitioners and 75.8 % preferred both sputum examination and chest x-ray for diagnosis of tuberculosis. 79% of private practitioners were aware of notification regarding TB case. Need for notification according to 63.3% of practitioners was to help in tracing contacts and further prevention of TB, follow up of patients (40%). Only 23.3% had heard of Nikshay. 42.5% referred patient to RNTCP and major reason was availability of free drugs (76.6%). Conclusions: The awareness and involvement of PPs regarding RNTCP & its initiatives were low. There is a need for measures to improve training and interactions with PPs by programme officers to insure their Maximum participation.